Investment in Natural Gas Pipelines in the Southern Cone of Latin America - Jadresic, Alejandro (World Bank, Washington, DC, 2015)
Increasing demand for clean energy sources is expanding investment in natural gas infrastructure around the world. Many international projects involve pipelines connecting energy markets in two or more countries. A key feature of investment taking place in Latin America is the convergence of gas and electricity markets. Many projects are being developed to supply gas to new power generation plants needed to meet electricity demand. Construction of a pipeline over the Andes mountains to supply gas from Argentina to energy markets in central Chile was an idea long unfulfilled for political, economic, and technical reasons. Great changes have now taken place in a very short time. The author discusses both the achievements and the challenges to be faced by pipeline developers and Chiles energy sector. He details the benefits of the cooperative effort to consumers in terms of lower energy prices, higher environmental standards, and a more reliable energy system. The experience in Latin Americas southern cone shows how technological innovation, economic deregulation, and regional integration make it possible to build major international gas pipeline projects within a competitive framework, and without direct state involvement.